1991
DOI: 10.1128/jb.173.7.2160-2166.1991
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression in Escherichia coli of the Serratia marcescens metalloprotease gene: secretion of the protease from E. coli in the presence of the Erwinia chrysanthemi protease secretion functions

Abstract: The Serratia marcescens extraceliular protease SM is secreted by a signal peptide-independent pathway. When the prtSM gene was cloned and expressed in Escherichia coli, the cells did not secrete protease SM. The lack of secretion could be very efficiently complemented by the Erwinia chrysanthemi protease B secretion apparatus constituted by the PrtD, PrtE, and PrtF proteins. As with protease B and a.-hemolysin, the secretion signal was located within the last 80 amino acids of the protease. These results indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
56
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 44 publications
4
56
2
Order By: Relevance
“…ExpE1 contained 15 copies of the nonapeptide repeat (X[I/L]X[A/G]GXGXD) which was proposed to be implicated in the binding of Ca 2ϩ (51,83). These repeats were also found in NodO (12 copies) and other secreted proteins such as hemolysin (15 copies) and several proteases (4 copies) (20,26,49). After the last nonapeptide repeat, two highly conserved positions containing the aromatic residue tyrosine or phenylalanine were present in ExpE1 and the related proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ExpE1 contained 15 copies of the nonapeptide repeat (X[I/L]X[A/G]GXGXD) which was proposed to be implicated in the binding of Ca 2ϩ (51,83). These repeats were also found in NodO (12 copies) and other secreted proteins such as hemolysin (15 copies) and several proteases (4 copies) (20,26,49). After the last nonapeptide repeat, two highly conserved positions containing the aromatic residue tyrosine or phenylalanine were present in ExpE1 and the related proteins (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We previously cloned a S. marcescens 4.2-kb DNA fragment coding for two inner membrane proteins-PrtDSM (a membrane ATPase) and PrtEsM, both required for the secretion of the S. marcescens metalloprotease (PrtSM) in E. coli via a signal peptide-independent pathway (6,16). In addition, this 4.2-kb insert encodes a third protein, HasA, of apparent molecular mass 19 kDa, which was secreted in large amounts (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies were raised in a rabbit against pure HasA protein and used in Western blot analysis (13) at a 1:2000 dilution. The other rabbit sera used have been described (14)(15)(16). For growth experiments, the sera were heated at 56TC for 10 min to inactivate complement.…”
mentioning
confidence: 99%
“…The genes encoding the secretion device for the extracellular protein lacking the signal sequence have been reported in several bacteria: the E. coli hlyBC and tolC genes (2,27,45,48) for hemolysin, the prtDEF EC genes (21) for the metalloprotease in E. chrysanthemi, the aprDEF genes for Pseudomonas aeruginosa alkaline protease (12), the cyaBDE genes for cyclolysin of B. pertussis (10), and the lktBD genes for the P. haemolytica leukotoxin (42). It has been reported that the cells carrying the hlyBC and tolC or prtDEF EC genes secrete some of the extracellular proteins described above (3,8,22,28,39) and that the genes encoding the secretory apparatus for these proteins are similar to the hlyBC and tolC or prtDEF EC genes. Recently, the hasD and hasE genes coding for two components HasD and HasE, a secretion device for the S. marcescens metalloprotease, have been cloned, respectively (23).…”
mentioning
confidence: 99%